Innovation in the Circular Economy in the Water Sector: A Case Study on Wabag Water Services Romania - Daniela STAICU (Revista de Management Comparat International)
In Romania, only 12% of urban wastewater meets EU treatment standards, with over 50% originating from commercial and industrial activities containing pollutants like heavy metals, highlighting the urgent need for improved wastewater treatment infrastructure. Literature about best practices of wastewater treatment in Romania to positively impact the circular economy are lacking. The paper's objective is to be informed by observations about the resource recovery model in the wastewater management sector. Drawing from the insights gathered in the literature review, this paper aims to explore the following research questions: "What are the best practices in wastewater treatment in Romania that can positively influence the circular economy?", "What obstacles hinder the transition of wastewater treatment businesses to a circular model?", "What opportunities exist for rethinking the operations of wastewater treatment businesses to align with a circular model?". The research employs qualitative research methods, specifically a descriptive case study. To ensure a thorough, accurate, and impartial analysis of the phenomenon under investigation, multiple data collection techniques were utilized, including an in-depth interview in two stages and the examination of public documents about the company’s activities.The global emphasis on ESG criteria highlights wastewater reuse and biogas generation as key to achieving SDG 6, promoting circular economies, sustainable urban planning, and SMART city development through multi-stakeholder collaboration. Addressing the challenges posed by this topic requires a multi-stakeholder approach involving government and regulatory bodies, water utility companies, industry, environmental organizations, researchers, technology providers, consumers and residents, urban planners and policy makers. In the near future, wastewater treatment plants are anticipated to transform into ecologically sustainable technological systems and become essential components of SMART cities.